EFIKASI PGPM Streptomyces sp. DAN Trichoderma sp. TERHADAP PERTUMBUHAN VEGETATIF TANAMAN TOMAT CHERRY (Lycopersicum cerasiformae Mill.) - Najvania Nawaal; Guniarti Guniarti; Ida Retno Moeljani (Plumula : Berkala Ilmiah Agroteknologi, 2021)
Cherry Tomato Plant (Lycopersicum cerasiformae Mill.) Is a well-known horticultural commodity with high benefits and high selling power. This study aims to determine the efficacy of PGPM Streptomyces sp. and Trichoderma sp. on the vegetative growth of cherry tomato plants as well as The purpose of this study was to determine the efficacy of PGPM on the vegetative growth of cerry tomato plants. Cherry tomato plants are planted in polybags on the land of the Faculty of Agriculture, Veterans National Development University, East Java. This study used a single randomized block design with 5 treatments repeated 4 times. The treatment consisted of P₀ : K = Control (without giving PGPM), P₁: S = PGPM (1) Streptomyces sp. given with a concentration of 20 ml., P₂ : T = PGPM (1) Trichoderma sp. given with a concentration of 20 ml., P₃ : ST 2:2 = PGPM (2) Streptomyces sp. : (2) Trichoderma sp. given at a concentration of 20 ml., P₄ : ST 3:1 = PGPM (3) Streptomyces sp. : (1) Trichoderma sp. given at a concentration of 20 ml / 1.000 ml aquadest. The results showed that PGPM with the concentration and dose applied to cerry tomato plants had not had an effect on plant height and number of leaves.